Echocardiographic pattern of rheumatic valvular disease in a contemporary sub-Saharan African pediatric population: an audit of a major cardiac ultrasound unit in Yaounde, Cameroon. Issue 1 (December 2016) - Nkoke, Clovis; Lekoubou, Alain; Dzudie, Anastase; Jingi, Ahmadou; Kingue, Samuel; Menanga, Alain; Kengne, Andre
Abstract Background Rheumatic Heart Disease (RHD) remains a major cause of childhood acquired heart disease in developing countries. However reported echocardiographic features are limited to a few countries. This report is on the demographic and echocardiographic features of RHD in children using data from the largest referral hospital in Yaounde, the capital city of Cameroon. Methods The register of the cardiac ultrasound unit of the Yaounde General Hospital for the period 2003–2013 served as basis for data collection. RHD diagnosis was based on the World Heart Federation Criteria for the diagnosis of RHD. Demographic data, pattern of valve lesions and severity were analyzed. Results A total of 1130 first echocardiographic examinations were performed in children aged ≤ 18 years. Sixty-five (5.8 %) had a definite echocardiographic diagnosis of RHD with their mean age being 11.8 years (SD 3.6) and 31 (47.1 %) being boys. The commonest primary reasons for requesting an echocardiographic examination were a clinical diagnosis of RHD (24.6 %) without heart failure, a clinical diagnosis of heart failure (24.6 %), and heart murmurs (21.5 %). Isolated mitral regurgitation was the most common valve lesion (49.2 %) and was frequently associated with aortic regurgitation (35.4 %). Severe lesions were found in 63.3 % of participants. No right heart lesion was reported. Conclusions A sizable proportion of children undergoing echocardiographic examination at this major referral hospital in Cameroon had RHD, with lesions found only on the left heart. These lesions predominated on the mitral valve, were commonly associated with aortic regurgitation, and more often severe.